Kejadian Emesis Gravidarum pada Ibu Hamil Trimester I di Desa Suciharjo Kecamatan Parengan Kabupaten Tuban - Agoesta Pralita Sari; Isnaini Novitasari; Alfina Meila Dwi Cahyani (Indonesian Health Science Journal, 2023)
Introduction : The incidence of emesis gravidarum or nausea and vomiting that occurs in pregnant women is something that should not be taken lightly. This can be fatal and have a negative impact on the health of the mother and fetus. Objective : This study aims to determine the incidence of emesis gravidarum in first trimester pregnant women in Suciharjo Village, Parengan District, Tuban Regency. Method : The design used in this research is descriptive. The sample was 45 pregnant women in the first trimester. Data collection used was using the Rhodes Index For Nausea, Vomiting, And Retching (RINVR) questionnaire with a sampling technique using purposive sampling. Results : Nearly half of pregnant women in the first trimester in Suciharjo village, Parengan district, Tuban regency experienced severe nausea and vomiting. Conclusion : Description of the incidence of emesis gravidarum in first trimester pregnant women in Suciharjo village, Parengan district, Tuban regency, almost half of whom experienced severe nausea and vomiting.